O CONTROLE DE CONSTITUCIONALIDADE NO BRASIL: republicanismo em uma sociedade aberta de intérpretes uma análise do discurso a partir de casos concretos - Santos, Gustavo André dos (2015)
This theses aims to analyze the inter-institutional dialogue from the complex relationship between law and politics. It starts with an understanding of deliberative democracy from the tension between popular sovereignty and fundamental rights, as is proposed by the philosopher Jürgen Habermas. Therefore, it is sought to reconstruct the Brazilian constitutional history and strengthening the role of the judiciary over time, pointing out the problems that this stance produced in relations between the powers and the assumption of responsibilities by the Executive and the Legislature and the civil society, about the effectiveness of the Constitution. The rhetoric of "guardian of the Constitution" of the Supreme Court is analyzed in the broader context of democracy and the expansion of this apex body of the Judiciary. It points out how the enhanced model of judicial review into force accentuates one pole of the tension between public and private autonomy. Finally, it is sought to demonstrate that the recognition of a dialogical perspective in the constitution reading can contribute to increasing the legitimacy of the current judicial review, particularly in the complex relationship between constitutionalism and democracy, and foster the development of a feeling constitutional in Brazilian society.